Galien et le lait - Wilkins, John (Food & History, 2015)
Abstract This paper examines Galen’s study of the qualities of milk. He breaks down the strict division between urban and rural life, and, as in Hippocratic thought, he believes that nature (phusis) determines whether what we eat will be good or bad; he distinguishes between different sorts of milk, as produced by women or animals. The quality is determined by variation in food, different constitutions and differentiation in age, when milk may be good or bad, even for townsmen. Abstract L’analyse montre comment, en traitant des propriétés du lait, Galien rompt avec la séparation trop grande des produits de la ville et des produits de la campagne. Pour le médecin, héritier des conceptions de la médecine hippocratique, c’est la nature (phusis) qui détermine l’action bonne ou mauvaise d’un aliment ; il distingue ainsi les sortes de lait selon l’alimentation de la femme ou des animaux qui le produisent, des constitutions et des âges de la vie où cet aliment est nocif ou profitable, même en ville.